Enhanced Mucosal Antibody Production and Protection against Respiratory Infections Following an Orally Administered Bacterial Extract - Pasquali, Christian; Salami, Olawale; Taneja, Manisha; Gollwitzer, Eva S.; Trompette, Aurelien; Pattaroni, Céline; Yadava, Koshika; Bauer, Jacques; Marsland, Benjamin J. (Frontiers in Medicine, 2014)
Secondary bacterial infections following influenza infection are a pressing problem facing respiratory medicine. Although antibiotic treatment has been highly successful over recent decades, fatalities due to secondary bacterial infections remain one of the leading causes of death associated with influenza. We have assessed whether administration of a bacterial extract alone is sufficient to potentate immune responses and protect against primary infection with Influenza, and secondary infections with either Streptococcus pneumoniae or Klebsiella pneumoniae in mice. We show that oral administration with the bacterial extract, OM-85, leads to a maturation of dendritic cells and B cells characterised by increases in MHC II, CD86, CD40 and a reduction in ICOSL. Improved immune responsiveness against Influenza virus reduced the threshold of susceptibility to secondary bacterial infections, and thus protected the mice. The protection was associated with enhanced polyclonal B cell activation and release of antibodies that were effective at neutralising the virus. Taken together, these data show that oral administration of bacterial extracts provides sufficient mucosal immune stimulation to protect mice against a respiratory tract viral infection and associated sequelae.